Stability analysis of compressed air energy storage in underground space: a comparative research of coal mine roadway and salt cavern - Fan, Jinyang; Guo, Pengyu; Wang, Yifan; Li, Zongze; Zou, Yang; Jiang, Deyi; Nelias, Daniel (Geomechanics for energy and the environment, 2025)
The application of Compressed Air Energy Storage (CAES) in large-scale projects offers a promising solution for mitigating fluctuations in renewable energy generation. Focusing on the CAES project in Yungang coal mine, Datong, Shanxi, this study qualitatively and quantitatively investigated the impact of creep and cyclic loading on the roadway under various CAES operating frequencies. Stability indicators for Compressed Air Energy Storage Roadways (CAES-R), including displacement contours, roof subsidence, volume shrinkage, etc., were compared at different CAES operating frequencies, and the stability of CAES-R was compared to salt cavern CAES. Results reveal that higher CAES operating frequencies correspond to lower roadway deformation and plastic damage. After ten years of simulation with daily operation frequency, roof subsidence reaches approximately 20mm, with a volume shrinkage of 0.76%. Under the reduced frequency of once every 10 days, roof subsidence reaches 33mm and volume shrinkage 1.05% after ten years. Junction sections exhibited greater deformation than non-junction sections, demonstrating higher susceptibility to structural failure. Most deformation and damage occur rapidly during early operation stages, accumulating more slowly thereafter. A novel comparative analysis between CAES-R and traditional salt cavern CAES indicates CAES-R reservoirs exhibit significantly lower volumetric shrinkage rates and smaller plastic zones than the comparative study. Taking various factors into consideration, CAES-R also has better prospects than salt cavern CAES. It should be noted that the general applicability of these findings requires further site-specific evaluation due to geological heterogeneity and operational constraints.